DEVELOPMENT OF MATHEMATICS CURRICULUM IN PREPARATION FOR INDONESIA'S GOLDEN AGE 2045 - Pratiwi, Tarizka; Barkah, Siti; Sutirna, Sutirna (Jurnal Numeracy, 2025)
The purpose of this article is to discuss the curriculum that must be developed to address challenges and seize opportunities in the era of Golden Indonesia 2045, with a focus on critical thinking skills, technology integration, and contextual approaches. The method used is library research. Data sources were obtained from relevant literature, including books, journals, and scientific articles on the selected topic. The discussion results show that technology-based learning innovations, such as software and adaptive learning systems, can be a solution for improving students' mathematical literacy. In addition, a contextual approach that integrates mathematical concepts with other fields can prepare students to address real problems in the digital era. The conclusion of this article is that developing a mathematics curriculum for Indonesia Emas 2045 must focus on improving critical thinking skills, contextualizing material, and integrating technology into learning. By overcoming challenges such as the technology gap, teaching quality, and prior curriculum implementation, mathematics education is expected to produce a generation that is superior and competitive in the era of globalization.